SISTEM PENDIDIKAN DI NEGARA INDONESIA - Aisyah Jamil Al Ibrizi; Agus Faisal Asyha (CV JK Riset Publishing Group, 2026)
This study aims to analyze the Indonesian education system based on historical, philosophical, sociological, juridical, and curriculum aspects, as well as the roles of the government and society. The method used was library research with a descriptive qualitative approach. Data were obtained from laws and regulations, books, scientific articles, and educational policy documents. The results show that the Indonesian education system has developed based on the values of Pancasila and the 1945 Constitution and encompasses formal, non-formal, and informal education pathways. The curriculum continues to be refined to address the development of science and technology and societal needs. The study concludes that synergy among the government, society, families, and educational institutions is essential to achieving a high-quality, inclusive, and sustainable education system.